Bank Capital and Risk in Europe and Central Asia Ten Years After the Crisis - Anginer, Deniz; Demirguc-Kunt, Asli; Mare, Davide S. (World Bank, Washington, DC, 2020)
This paper examines changes in bank capital and capital regulations since the global financial crisis, in the Europe and Central Asia region. It shows that banks in Europe and Central Asia are better capitalized, as measured by regulatory capital ratios, than they were prior to the crisis. However, the increase in simple equity ratios for the same banks has been smaller over the past 10 years. The increases in regulatory capital ratios have coincided with a reduction in the stringency of the definition of Tier 1 capital and reduction in risk-weights. Further analyses show that bank risk in Europe and Central Asia is more sensitive to changes in simple leverage ratios than in regulatory capital ratios, consistent with the notion that equity ratios only include high-quality capital and do not rely on internal risk models to compute risk-weights. Although there has been some effort to increase capital and liquidity requirements for institutions deemed systemically important, the region has been lagging in addressing the resolution of these institutions.